2007
DOI: 10.1563/1548-1336(2007)33[133:ibaait]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Bone Augmentation After Infected Tooth Extraction Using Titanium Membranes

Abstract: Infectious process frequently results in extensive bone resorption and defect, periradicular or periapical lesions, or vertical fracture with infected sinus tract. When tooth extraction is mandated it typically results in additional bone loss in the buccal or lingual cortical plate. Immediate guided bone regeneration (GBR) and implant fixation at an infected site is frequently complicated by soft-tissue dehiscence, membrane exposure, and implant failure. The objective of this research is to assess the feasibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 13 publications
2
20
0
6
Order By: Relevance
“…PRF plugs can also be indicated in management of residual extraction sockets[95]. A technique in which autologous PRF is used in extracted socket after immediate bone augmentation using titanium membranes applied to the socket walls and achieving primary closure, was found to be feasible and safe with adequate bone filling after 8 wk or above for implant fixation[96]. Hafez et al[97] in 2015 demonstrated that PRF membrane maintains particulate autogenous bone graft and help achieve primary coverage over immediately placed implants.…”
Section: Application Of Pc In Periodontics and Implant Dentistrymentioning
confidence: 99%
“…PRF plugs can also be indicated in management of residual extraction sockets[95]. A technique in which autologous PRF is used in extracted socket after immediate bone augmentation using titanium membranes applied to the socket walls and achieving primary closure, was found to be feasible and safe with adequate bone filling after 8 wk or above for implant fixation[96]. Hafez et al[97] in 2015 demonstrated that PRF membrane maintains particulate autogenous bone graft and help achieve primary coverage over immediately placed implants.…”
Section: Application Of Pc In Periodontics and Implant Dentistrymentioning
confidence: 99%
“…[15] Use of autologous PRF in extracted socket filling after immediate bone augmentation using titanium membranes applied to the socket walls and primary closure was found to be feasible and safe with adequate bone filling after 8 weeks or above for implant fixation. [16]…”
Section: Clinical Applicationmentioning
confidence: 99%
“…En odontología se ha utilizado para la regeneración de tejidos posterior a alguna intervención (Blus et al, 2008), incluyendo tejido blando y hueso (Consolo et al, 2007), con resultados clínicamente significativos, aunque en ciertos tipos de cirugías su uso no está tan evidenciado (Kfir et al, 2007) o que simplemente demuestran resultados contradictorios o negativos en lo que ha cicatrización se refiere (Torres et al, 2009) lo que permite establecer la discusión sobre la real efectividad de este procedimiento e contextos clínicos.…”
Section: Introductionunclassified
“…En odontología se ha utilizado para la regeneración de tejidos posterior a alguna intervención (Blus et al, 2008), incluyendo tejido blando y hueso (Consolo et al, 2007), con resultados clínicamente significativos, aunque en ciertos tipos de cirugías su uso no está tan evidenciado (Kfir et al, 2007) Por lo cual, el objetivo de este estudio radica en evaluar la efectividad del plasma rico en plaquetas en la cicatrización de implantes dentales mediante un procedimiento de revisión sistemática que deriva en un metaanálisis permitiendo generar una recomendación clínica basada en la evidencia.…”
Section: Introductionunclassified